2022
DOI: 10.1590/acb370605
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrolysin alleviates early brain injury after traumatic brain injury by inhibiting neuroinflammation and apoptosis via TLR signaling pathway

Abstract: Purpose: Traumatic brain injury (TBI) is a major cause of death and disability. Cerebrolysin (CBL) has been reported to be anti-inflammatory by reducing reactive oxygen species (ROS) production. However, the neuroprotection of CBL in TBI and the potential mechanism are unclear. We aimed to investigate the neuroprotection and mechanisms of CBL in TBI. Methods: The TBI model was established in strict accordance with the Feeney weight-drop model of focal injury. The neurol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…After chronic sciatic nerve constriction in rats, a functional imbalance between proapoptotic BAX and antiapoptotic BCL2 has been identified (Maione et al, 2002). The decrease in the BAX/BCL2 ratio emphasizes the antiapoptotic effect of Cerebrolysin (Lu et al, 2022), the antiapoptotic effect of local dexamethasone in agreement with previous studies (Hoang et al, 2009;Lee et al, 2015), and the antiapoptotic effect of vitamin C to adapt or overcome Sciatic nerve injury (Sourour et al, 2012;Gong et al, 2022). Similarly, 10.3389/fnana.2023.1090738 the antiapoptotic effect of vitamin C was superior to Cerebrolysin and dexamethasone, which may be referred to as its ability in neutralizing free radicals and ameliorating oxidative stress-mediated cellular apoptosis and cell death.…”
Section: Discussionmentioning
confidence: 99%
“…After chronic sciatic nerve constriction in rats, a functional imbalance between proapoptotic BAX and antiapoptotic BCL2 has been identified (Maione et al, 2002). The decrease in the BAX/BCL2 ratio emphasizes the antiapoptotic effect of Cerebrolysin (Lu et al, 2022), the antiapoptotic effect of local dexamethasone in agreement with previous studies (Hoang et al, 2009;Lee et al, 2015), and the antiapoptotic effect of vitamin C to adapt or overcome Sciatic nerve injury (Sourour et al, 2012;Gong et al, 2022). Similarly, 10.3389/fnana.2023.1090738 the antiapoptotic effect of vitamin C was superior to Cerebrolysin and dexamethasone, which may be referred to as its ability in neutralizing free radicals and ameliorating oxidative stress-mediated cellular apoptosis and cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies are currently evaluating Cerebrolysin efficacy for other conditions, including cerebral palsy, vascular dementia, aneurysmal subarachnoid haemorrhage, and anosmia [ 66 ]. The main pharmacological effect of Cerebrolysin is the restoration of the surrounding and damaged nerve structures, which is deleterious to neurons, causing their degeneration, dysfunction, and death [ 67 ]. Few articles have demonstrated the safety and efficacy of this drug, but noteworthy is a meta-analysis that demonstrated that this blend of peptides can be used as a safe therapy for recovery from severe traumatic brain injury.…”
Section: Discussionmentioning
confidence: 99%
“…To further confirm whether this increase in neuronal survival was associated with anti-apoptotic effects, we performed FJB and TUNEL staining on frozen sections of rat tissue. Both domestic and foreign scholars have used the TUNEL technique to detect DNA fragments formed by apoptosis and found that only a large number of TUNEL-positive cells could be seen in the peripheral area of the injury foci, while no TUNEL-positive cells were expressed in the core necrotic area and the peripheral normal area [ 36 ]. The same was observed in our experiments, wherein, in the Sham group, only few, if any, FJB- and TUNEL-positive apoptotic cells could be seen; in the TBI and TBI+vehicle groups, the number of apoptotic cells was significantly increased; while in the NGR1 treatment groups, the number of apoptotic cells in rat neurons was significantly reduced.…”
Section: Discussionmentioning
confidence: 99%